2022
DOI: 10.3389/fnut.2022.934951
|View full text |Cite
|
Sign up to set email alerts
|

The role of metabolites under the influence of genes and lifestyles in bone density changes

Abstract: PurposeOsteoporosis is a complex bone disease influenced by numerous factors. Previous studies have found that some metabolites are related to bone mineral density (BMD). However, the associations between metabolites and BMD under the influence of genes and lifestyle have not been fully investigated.MethodsWe analyzed the effect of metabolites on BMD under the synergistic effect of genes and lifestyle, using the data of 797 participants aged 55–65 years from the Taizhou Imaging Study. The cumulative sum method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Several previous studies have indicated that a plant-based diet may have a negative impact on bone health, which is consistent with our findings. For instance, a Chinese cohort study reported significant differences in hPDI between three groups (normal, osteopenia, and osteoporosis), with the normal group having a significantly lower hPDI than the osteopenia and osteoporosis groups [ 27 ]. In an Iranian case–control study of post-menopausal women with osteoporosis, a higher uPDI was associated with an increased risk of bone loss in the femoral neck (OR: 2.63; 95% CI: 1.37–5.06) and lumbar spine (OR: 4.23; 95% CI: 2.19–8.19) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have indicated that a plant-based diet may have a negative impact on bone health, which is consistent with our findings. For instance, a Chinese cohort study reported significant differences in hPDI between three groups (normal, osteopenia, and osteoporosis), with the normal group having a significantly lower hPDI than the osteopenia and osteoporosis groups [ 27 ]. In an Iranian case–control study of post-menopausal women with osteoporosis, a higher uPDI was associated with an increased risk of bone loss in the femoral neck (OR: 2.63; 95% CI: 1.37–5.06) and lumbar spine (OR: 4.23; 95% CI: 2.19–8.19) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have used the three indexes to examine the association between a plant-based diet and BMD. Despite some initial research conducted in Iranian and Chinese populations, the association between plant-based dietary indexes and BMD is still not well understood, and the findings are inconsistent [ 26 , 27 ]. Further studies with larger sample sizes and diverse populations are needed to better elucidate this relationship and its potential implications.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, recent studies have shown that HDL-C can negatively affect osteogenic differentiation by removing oxysterols from peripheral tissues, further suggesting a role in bone health ( Y. Yang et al, 2018 ). Secondly, two studies conducted within a Chinese population have supported the beneficial impact of VLDL on bone health ( Lv et al, 2022 ; You et al, 2014 ). Moreover, investigations conducted using two separate cohorts (UK Biobank and MrOS) have revealed a positive correlation between valine levels and BMD at the femoral neck ( Grahnemo et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…A dual-energy X-ray absorptiometry (Lunar DPX NT-400157; GE Healthcare, Madison, WI, United States) was employed for the assessment of BMD at the lumbar spine (L1-L4), total hip, and the femoral neck ( Lv et al, 2022 ). BMD is measured by an experienced physician using the same instrument, and strictly following the manufacturer's guidelines for equipment usage ( Jiang et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%